HUBUNGAN USIA, PENDIDIKAN DAN PARITAS TERHADAP PENGETAHUAN IBU PASCAPERSALINAN TENTANG MOMMY’S THUMB - Tiffany Atia Aristi; Ayu Permata (Ensiklopedia of Journal, 2026)
Background: Mommy’s Thumb is a common condition among postpartum mothers that may affect daily activities and infant care. Adequate knowledge is essential for early prevention and management. Maternal characteristics such as age, education, and parity may influence postpartum mothers’ knowledge. Objective: This study aimed to examine the relationship between age, education, and parity and postpartum mothers’ knowledge of Mommy’s Thumb. Methods: A cross-sectional study was conducted at the Independent Midwifery Practice of Bd. Yuzi Harina, S.Keb. Postpartum mothers who met the inclusion criteria were recruited as participants. Data were collected using a structured questionnaire. Statistical analysis was performed to determine the relationship between age, education, parity, and knowledge level, with a significance level of p 0.05. Results: Age, education level, and parity were significantly associated with postpartum mothers’ knowledge of Mommy’s Thumb. Higher education, multiparity, and older age were related to better knowledge levels. Conclusion: Age, education, and parity are associated with postpartum mothers’ knowledge of Mommy’s Thumb. Strengthening health education during postpartum care is recommended. Keywords: age, education, parity, postpartum mothers, Mommy’s Thumb